HUKUM & GLOBALISASI: IMPLEMENTASI PERDA PROVINSI BALI NO. 5 TAHUN 2005 TENTANG PERSYARATAN ARSITEKTUR BANGUNAN GEDUNG TERHADAP PERGESERAN PARADIGMA BERARSITEKTUR DI BALI - I Kadek Pranajaya (Jurnal Aktual Justice, 2021)
The architectural style of buildings in Bali must be able to display the traditional Balinese architectural style (ATB) that is in harmony, balanced and integrated with the environment based on Balinese culture. Globalization and modernization encourage the creation of new technologies in the building materials industry to be more effective and efficient. Through a sociological juridical approach, it was found that the influence of globalization and modernization caused a shift in the architectural paradigm in Bali. Globalization and modernization have led to an identity crisis and the degradation of ATB towards a modern and minimalist direction as well as disharmony of traditional values ​​as the ancestral heritage of the people in Bali. The architectural paradigm shift in Bali has begun to shift and has deviated from the existing rules. The results of the study indicate that there has been a violation of the provisions on building architecture that have been stipulated through the Bali Provincial Regulation No. 5, 2005. Violations that take place seem to be left unchecked, ignorance or also a lack of public understanding of the norms that have been set. This is caused by the legal structure, legal substance and legal culture not working properly.